Case Study of Giving Small White Ginger Drink (Zingiber Officinale Var Amarum) to Hypertensive Respondents - Tsani , Averose Millania; Rofiqi, Erfan; Mukarromah, Nur; Wijaya, Siswanto Agung (Indonesian Academia Health Sciences Journal, 2022)
Background: Hypertension with increasing age 45-59 years, the possibility of someone suffering from hypertension is also greater. Hypertension if not treated immediately can cause heart failure, stroke and kidney failure. So far, hypertension treatment is done pharmacologically (with drugs) or with non-pharmacological therapy (without drugs). One of the non-pharmacological therapies to control blood pressure is by giving ginger drink (zingiber officiale). Purpose: The purpose of this study was to determine the results of the application of ginger drink (zingiber officiale) to respondents with hypertension. Method: The research design used is descriptive with a case study approach. The case study was conducted by giving ginger drink then measuring blood pressure before and after giving ginger drink, the number of respondents was 3 people, ginger drink was given for 5 days, respondents consumed 100 cc of ginger drink in the morning. How to make boiled ginger water by weighing small white ginger (4 grams), then clean the small white ginger and cut it into small pieces, then heat 200 cc of water for ± 10 minutes and add the ginger, after that the boiled ginger water is filtered into 100 cc and ready to serve. Results: The results of the study showed that respondent 1 experienced a decrease in blood pressure from 150/92 mmHg to 135/76 mmHg (high normal), respondent 2 experienced a decrease in blood pressure from 150/90 mmHg to 130/80 mmHg (high normal) and respondent 3 experienced a decrease in blood pressure from 160/100 mmHg to 142/80 mmHg (grade 1 hypertension). Conclusion: Giving small white ginger drink (zingiber officinale var amarum) can lower blood pressure. Giving ginger drink can be used as a complementary therapy solution for treating hypertension